KOMPOSIT DENGAN MATRIK SODIUM SILIKAT DAN PENGISI SENG OKSIDA SEBAGAI THERMAL GREASE UNTUK CENTRAL PROCESSING UNIT (CPU) - Hasan, Abu (Politeknik Negeri Sriwijaya, 2018)
Sodium silicate has a higher thermal conductivity and lower viscosity than the basic material for making thermal grease that is widely used today, silicon. On the other hand, ceramic materials such as zinc oxide have many advantages compared to metals as thermal grease fillers which are widely used today. Composites with sodium silicate matrix and zinc oxide fillers were studied as thermal grease for central processing units. This research aims to produce thermal grease for CPU that have better quality than those on the market today. Thermal grease was made by mixing nanosized zinc oxide fillers and sodium silicate matrix with filler concentrations of 16 wt%, 18 wt%, and 20 wt% and tested by application-specific test method. The results of the study show an increase in thermal conductivity to the increase in filler fractions. Thermal grease with 20 wt% fillers produces thermal grease with the highest and most stable thermal conductivity.